A domain in human EXOG converts apoptotic endonuclease to DNA-repair exonuclease - Michal R. Szymanski (Nature Portfolio, 2017)
Human EXOG is crucial for mitochondrial DNA repair. Here the authors present the crystal structures of hEXOG in apo form and as DNA complex and suggest a `tape-measure' activity to generate optimal substrates for mitochondrial base excision repair.